2021
DOI: 10.1186/s12913-021-07308-0
|View full text |Cite
|
Sign up to set email alerts
|

Equity of health care financing in South Korea: 1990–2016

Abstract: Background The National Health Insurance in Korea has been in operation for more than 30 years since having achieved universal health coverage in 1989 and has gone through several policy reforms. Despite its achievements, the Korean health insurance has some shortfalls, one of which concerns the fairness of paying for health care. Method Using the population representative Household Income and Expenditure Survey data in Korea, this study examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Such improvements were in part due to better access to high-quality healthcare; National Health Insurance (NHI) was enacted in 1963 and coverage extended to the majority of the population by 1989 3 . It is now characterized as universal population coverage with a single-payer system since 2000 4 . However, the rate of decline in TB incidence slowed during the 2000s such that the incidence of TB was similar in 2001 and 2011, at 96.3 cases per 100,000, and 100.8 cases per 100,000 population, respectively 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Such improvements were in part due to better access to high-quality healthcare; National Health Insurance (NHI) was enacted in 1963 and coverage extended to the majority of the population by 1989 3 . It is now characterized as universal population coverage with a single-payer system since 2000 4 . However, the rate of decline in TB incidence slowed during the 2000s such that the incidence of TB was similar in 2001 and 2011, at 96.3 cases per 100,000, and 100.8 cases per 100,000 population, respectively 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Taking the Republic of Korea as an example, their overall healthcare financing system was regressive, not only for OOP payments, but also for its National Health Insurance and private health insurance scheme. This was due to high OOP payments made by their population regardless of their socioeconomic status as copayments for healthcare services that are not covered under either national and private health insurance, such as for expensive oncological medications and diagnostics [36]. The same scenario can be seen in other developed European countries, such as Austria, in which the OOP healthcare payments were regressive.…”
Section: Discussionmentioning
confidence: 93%
“…In another country within the region, South Korea, a developed high-income country, a survey-based study based on household data from 1990 to 2016 emphasizes the significance of the healthcare insurance system and its impact on fair distribution of financial burden [28]. The study revealed a weak regressivity in OOP expenditures, which may not affect individuals with low incomes in terms of access to doctors or outpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, the high-income country of this region, Tae-Jin Lee et al (2021) conducted a study to assess the vertical equity of healthcare financing over a considerable timeframe between 1990 and 2016 [28]. Their findings revealed that direct tax was the most progressive mode of healthcare financing, while OOP payments were consistently weakly regressive.…”
Section: East Asiamentioning
confidence: 99%
See 1 more Smart Citation